Prognostischer Wert der kardiovaskulären MRT bei Diabetikern = Prognostic value of cardiovascular MRI in diabetics - Schlett, Christopher L.; Bertheau, Robert; Kauczor, Hans-Ulrich; Weckbach, Sabine (Der Radiologe, 2015)
Clinical/methodical issueDespite an increased cardiovascular risk in patients with diabetes mellitus they are a heterogeneous population with very different individual manifestation of diseases; therefore, a profound stratification is recommended.Standard methodsClinical examinations and blood biomarkers are typically used in diabetic patients to determine the risk for developing cardio-cerebrovascular events.Methodical innovationsCardiac as well as whole-body magnetic resonance imaging (MRI) including cardiovascular sequences are established methods for clinical diagnostics. Their significance in predicting the outcome and the corresponding risk stratification for patients with diabetes is becoming increasingly more important based on recent study results.PerformanceLate gadolinium enhancement (LGE) in cardiac MRI detects silent myocardial ischemia in up to 30 % of diabetic patients, which is associated with a hazard ratio of 3-6 for cardiovascular events. Regional left ventricular wall motion abnormalities and decreased ejection fraction also have a prognostic value in diabetics. Based on whole-body MRI, the vessel score as well as carotid artery stenosis have been evaluated as additional predictors for cardio-cerebrovascular events.AchievementsThe MRI-based predictors have independent and incremental prognostic value beyond traditional risk stratification for cardio-cerebrovascular events; however, only the comprehensive assessment of whole-body MRI including angiography allows the identification of patients who remain free of cardio-cerebrovascular events over a period of 6 years.Practical recommendationsCardiac MRI, particularly the detection of LGE, can be recommended for risk stratification of patients with diabetes mellitus. The clinical relevance of the added prognostic value of whole-body MRI needs to be clarified in further studies.